Investigating bacterial diversity involved in the production of vegetable-based ethnic fermented food of North Bengal and their metabolic pathways with reverse ecology approach - Ghatani, Kriti; Sha, Shankar Prasad; Thapa, Subarna; Sarkar, Indrani; Sen, Gargi; Sen, Arnab (Frontiers in Sustainable Food Systems, 2024)
Endemic fermented vegetables play a crucial role in local cuisine and culture, with traditionally fermented raw green vegetables such as gundruk being a popular practice in North Bengal and Sikkim, India. However, there is a gap in the microbial profiling of these vegetables. This study aimed to explore the diversity of dominant bacterial populations in fermented leafy vegetables using both culture-dependent and culture-independent methods. In addition to isolating bacteria using conventional methods, we conducted phenotypic and biochemical characterization, community DNA isolation, and amplicon sequencing. We also introduced a new approach in bioinformatics analysis: reverse ecology, which analyzes complementation and competition among participant microbes. In conventional culture-dependent techniques, LAB genera such as Lactobacillus, Enterococcus, Leuconostoc, and Pediococcus have been identified as predominant consortia, whereas metagenomic analysis revealed that the microbiome of fermented dried leafy vegetables was mainly composed of Firmicutes, Proteobacteria, Actinobacteria, Bacteroides, and Planctomycetes at the phylum level. Within the Lactobacillaceae family, predominant types included Lactobacillus, Lactococcus, Pediococcus, Leuconostoc, Enterococcus, Vagococcus, Weissella, and Carnobacterium. The microbial metabolism revealed key pathways, such as carbon metabolism, glycolysis, gluconeogenesis, and glyoxylate. Aromatic amino acid degradation, fatty acid metabolism, amino sugar metabolism, nucleotide sugar metabolism, and biosynthesis of nucleotide sugar pathways were also active. The competition index among microbes and human metabolic data was low (0.32–0.44), indicating minimal competition for nutrition. Complementation indices between bacteria and humans were high (0.76–0.88), suggesting a beneficial impact of gundruk microbial populations on human health.